Evaluasi Proses Pengelolaan, Pengurangan, dan Pemanfaatan Limbah B3 pada Industri Amonia PT Kaltim Parna Industri - Sihombing, Pretty Sartika; Cundaningsih, Nurvita (Jurnal Serambi Engineering, 2026)
This study aims to evaluate the performance of hazardous and toxic (B3) waste management, reduction, and utilization at PT Kaltim Parna Industri, an ammonia-producing industry, in relation to applicable regulatory requirements. The evaluation focuses on eight types of B3 waste generated in 2024 and covers waste identification and balance, packaging, hazard communication through symbols and labels, the design and facilities of the temporary storage facility (TPS), storage practices, and waste reduction and utilization efforts. A quantitative descriptive approach was applied using a checklist instrument and Guttman-scale scoring to compare existing conditions with the technical criteria stipulated in the regulations. The results indicate very high compliance in technical aspects, with the TPS building and storage system achieving 100% compliance and the implementation of symbols and labels also achieving 100%, while the packaging aspect reached 88.8%; however, minor gaps remain in the consistency of applying symbols and labels to each individual package. These findings suggest that the B3 waste management system at the studied facility is generally effective, yet it still requires strengthening in documentation and the standardization of field practices, and the evaluation framework can be applied to similar industries for periodic performance reviews and for reinforcing environmental management systems.